Adoption of soil organic carbon-enhancing practices: A case of two watershed sites in Ethiopia. - Ng'ang'a Karanja, Stanley; Mersha Gelaw, Fekadu; Nguru, Wilson; Girvetz, Evan Hartunian (International Center for Tropical Agriculture, 2020)
This study aimed at identifying the factors that determine the decision to adopt and the intensity of adoption of soil organic carbon (SOC)-enhancing practices using two watershed sites in Ethiopia: Yiser (Amhara region) and Azugashube (Southern region). The study used survey data collected from 379 sample households drawn from four Kebele/village administrations at each watershed site. Multivariate and ordinary least squares regressions were used to identify the factors that determine the decision to adopt the SOC-enhancing practices and the factors that determine the extent of adoption of these practices, respectively. The study classified these various practices into three classes: soil and water conservation, agronomic, and agroforestry SOC-enhancing practices. We find that the decision to adopt soil and water conservation practices is negatively related to both the decision to adopt agronomic and to adopt agroforestry SOC-enhancing practices. On the contrary, we find that the decision to adopt agronomic and agroforestry practices is complementary. The study also identified diverse agroecological, farming system, institutional, and household characteristics that determine the decision to adopt and the intensity of adoption of the three SOCenhancing practices. Among the different variables, the study found location as a strong determinant of the type and intensity of adoption of the SOC practices.